Obesity, Unemployment, and Earnings - Härkönen, Juho; Räsänen, Pekka; Näsi, Matti (Nordic Journal of Working Life Studies, 2011)
The article analyses the effects of obesity—a clear signal of weight abnormality—on unemployment and earnings among Finnish men and women. Our empirical data consist of the last four waves (waves 4 to 8) of the Finnish section of the European Community Household Panel (ECHP) data collected between 1998 and 2001. According to our results, obese women have a significantly higher risk of unemployment (even after controlling for age, level of education and other related factors), than women who are not obese. Furthermore, the generally weaker occupational positions of obese women tend to translate to lower earnings. Overall, obese women are more likely to have weaker labour market attachment  and hold socio-economically weaker positions. Similar results were not found among men. Thus, our results indicate the presence of gender discrimination in the Finnish labour market. In the conclusions we further discuss weight related impacts on succeeding in the labour market, but also its role as a possible risk factor in drifting away from employment. We reflect on this issue as a form of inequality that can have an increasing significance in the future.